Mettre en situation et accompagner la construction de connaissances : un parti pris pour la formation à l’accompagnement de projets en agriculture - Lucie Gouttenoire; Marion Guillot (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article is about an experiment in agricultural higher education. Faced with change and uncertainty in agriculture, agricultural advisors need to deal with new stakes. For example, the profiles of people who want to set up a farm are changing, which requires to consider new ways of helping them to achieve their goals. How to help students to move towards such changing professions ? We consider that supporting students’ reflexivity is a good way to help them become responsible professionals who act in a relevant way in their working situations. In this paper, we describe a three-week study course that we have been teaching since 2012. Students are asked to help people who want to set up a farm, and to practice their reflexivity about this experiment. We have incrementally designed this study course on the basis of learning through our experience, confronting knowledge about education and participating in practice analysis devices. We describe this study-course as an application of interactive social constructivism. Students’ representations are considered as the starting point of our teaching job, socio-cognitive conflicts are encouraged and students’ reflexivity is fostered by simulating professional situations. This study-course has real strengths, but also some weaknesses that require further research. Thus there are debates about which types of knowledge count, and some students do not manage to really practice reflexivity.